The Efektivitas Model Pembelajaran STEM-Guided Inquiry Berbasis Kearifan Lokal "Dawet Ireng" Terhadap Literasi Sains Siswa Kelas VIII Pada Materi Unsur, Senyawa, dan Campuran: Efektivitas Model Pembelajaran STEM-Guided Inquiry Berbasis Kearifan Lokal "Dawet Ireng" Terhadap Literasi Sains Siswa Kelas VIII Pada Materi Unsur, Senyawa, dan Campuran - Elennita, Elennita; Indriyanti, Nurma Yunita; Nugraheni, Febriani Sarwendah Asri (PendIPA Journal of Science Education, 2025)
This study aimed to see the effectiveness of the STEM-Guided Inquiry learning model based on local wisdom dawet ireng on the science literacy of 8th grade students on elemental, compound, and mixed materials. The type of research used is a quasi-experiment with a pretest-postest control group design. The population of this study was all VIII grade students of SMPN 35 Purworejo, Purworejo Regency in the 2023/2024 school year. The samples of this study were Class VIII C and Class VIII D obtained by cluster random sampling technique. Class VIII C (30 students) as a control class and Class VIII D (30 students) as an experimental class. Data collection was carried out using test techniques in the form of science literacy essay questions and non-tests in the form of science literacy questionnaires. Data validity is obtained from validity tests and reliability tests. Prerequisite data analysis applies the kolmogorow-smirnov normality test and levene homogeneity test. The research hypothesis used the right side hypothesis test (one-tailed) through the independent sample t-test and assisted by the SPSS 22 program. The results showed that the value of t-count > t-table, that is 15.613> 1.672 with a significant level of 5%, so H1 is accepted. The n-gain improvement test results also showed that n-gain score of the experimental class was 0.577 (medium category) and the control class -0.037 (low category). Based on the results of research and data analysis, it is concluded that the STEM-Guided Inquiry learning model based on local wisdom dawet ireng effectively improves the science literacy of 8th grade students in elemental, compound, and mixture materials.